Least restrictive environment for students with disabilities - Kulig, Tanya (My University, 2009)
When assisting young people with disabilities, a collaborative approach involving student, parents, educators, and local and state service agencies is required in the development of services and supports. The educational placement of a student with disabilities continues to be an issue with parents, teachers, and student. An Individual Education Planning team comprised of teachers, parents, student and local and state service agencies decide where and how a student with disabilities will be educated to obtain the best educational practices in the least restrictive environment. Each student with an IEP should be looked at uniquely and individually as their needs and interests should be met when finding the most appropriate and effective educational setting. The educational environment should benefit the student with a disability as well as his or her peers in that setting.
Keywords: Students with disabilities; Children with disabilities -- Education